2017
DOI: 10.1111/sji.12564
|View full text |Cite
|
Sign up to set email alerts
|

sPD‐L1 Expression is Associated with Immunosuppression and Infectious Complications in Patients with Acute Pancreatitis

Abstract: Acute pancreatitis (AP) with infectious complications has high mortality because of early-stage immunosuppression. The programmed cell death-1 (PD-1)/programmed cell death ligand 1 (PD-L1) pathway is an important host immunosuppression mechanism. Soluble PD-L1 (sPD-L1) expression regulates co-inhibitory signals in malignancies or autoimmune disorders; however, its effects in AP are unknown. Here, we evaluated whether serum sPD-L1 is involved in immune dysfunction and assessed its relationship with infectious c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
4
18
2
Order By: Relevance
“…The other limitation was that there were no age‐matched healthy controls to compare their serum PD‐L1 level with those of patients with gastric cancer. Using the same ELISA kit as that used in the present study, Chen et al reported that the median serum PD‐L1 level in healthy controls was 48.15 pg/mL, which is very similar to the median serum PD‐L1 level reported in our series of patients with gastric cancer. Therefore, we suspect that there is no statistically significant difference in serum PD‐L1 level between healthy controls and patients with gastric cancer.…”
Section: Discussionsupporting
confidence: 87%
“…The other limitation was that there were no age‐matched healthy controls to compare their serum PD‐L1 level with those of patients with gastric cancer. Using the same ELISA kit as that used in the present study, Chen et al reported that the median serum PD‐L1 level in healthy controls was 48.15 pg/mL, which is very similar to the median serum PD‐L1 level reported in our series of patients with gastric cancer. Therefore, we suspect that there is no statistically significant difference in serum PD‐L1 level between healthy controls and patients with gastric cancer.…”
Section: Discussionsupporting
confidence: 87%
“…One of the limitations of the present study was the lack of healthy controls to compare sPD-L1 levels with those of patients with HBP cancer. Using the same ELISA kit that was used in the present study, Chen et al reported that the median serum PD-L1 level in healthy controls was 48.15 pg/ml [18]. The median serum PD-L1 level reported in our present study was slightly higher than this value.…”
Section: Discussioncontrasting
confidence: 47%
“…To conclude and validate this observation without a shadow of doubt, a larger cohort with control group is needed. Using the same ELISA kit that was used in the present study, Chen et al reported that the median serum PD-L1 level in healthy controls was 48.15 pg/ml [18]. The median serum PD-L1 level reported in our present study was slightly higher than this value.…”
Section: Discussioncontrasting
confidence: 47%